2014
DOI: 10.1016/j.envpol.2014.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Seagrasses as indicators for coastal trace metal pollution: A global meta-analysis serving as a benchmark, and a Caribbean case study

Abstract: 28Seagrass beds are highly productive coastal ecosystems providing a large array of 29 ecosystem services including fisheries and carbon sequestration. As seagrasses are known 30 to be highly sensitive to anthropogenic forcing, we evaluated the use of trace metal 31 concentrations in seagrasses as bioindicators for trace metal pollution of coastal regions at 32 both global and local scale. We carried out a meta-analysis based on literature data to 33 provide a global benchmark list for trace metal accumulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 54 publications
3
41
1
Order By: Relevance
“…Heavy metals may be incorporated into seagrass tissues from the water or sediments (Lyngby et al, 1982;Ward, 1987). The potential of heavy metal accumulation in seagrass has been investigated for bioremediation purposes (e.g., Bunluesin et al, 2007;Govers et al, 2014). Although some of elements are essential to plant growth (e.g., Cu, Fe, Mn, Ni, and Zn), several studies have shown that heavy metals negatively impact seagrass photosynthetic physiology (Prange and Dennison, 2000;Macinnis-Ng and Ralph, 2002;Papathanasiou et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals may be incorporated into seagrass tissues from the water or sediments (Lyngby et al, 1982;Ward, 1987). The potential of heavy metal accumulation in seagrass has been investigated for bioremediation purposes (e.g., Bunluesin et al, 2007;Govers et al, 2014). Although some of elements are essential to plant growth (e.g., Cu, Fe, Mn, Ni, and Zn), several studies have shown that heavy metals negatively impact seagrass photosynthetic physiology (Prange and Dennison, 2000;Macinnis-Ng and Ralph, 2002;Papathanasiou et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Increased bioaccumulation of heavy metal will give toxic and resistant effect for seagrass (MacInnis-Ng and Ralph, 2004). Heavy metals in seagrass may accumulate in seagrass grazing biota (Govers et al, 2014).…”
Section: Bioaccumulation Of Heavy Metalsmentioning
confidence: 99%
“…A better understanding of these pressures will allow managers to act at the source and reduce the degradation or improve the ecological quality of water bodies (Blanfuné et al, 2017). As proposed by Govers et al (2014), from a research perspective, it could be interesting to study the importance of seasonality and physiological status for the use of sea urchins and other marine organisms as bioindicators for TE pollution.…”
Section: Introductionmentioning
confidence: 99%